USING SEMANTIC MAPPING AS AN EFFORT TO IMPROVE THE READING ABILITY OF THE FOURTH GRADE STUDENTS OF SDN 005 LENGGADAI HILIR ROKAN HILIR - Gultom, Effendy; Rosdayanti, Rosdayanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2014)
Reading is one thenecessary skills that foreign languagelearners must achieve. Reading is not as simple as learning to spelland read sentences, but it is more complex than that. Readinginvolves the process of decoding, predicting, and many otherssimultaneously so that the reader can comprehend the text well.However, reading has become a ghost upon the students since itrequires the students to find some information within the text but thestudents are lazy to pay attention to it. Therefore, it is quitechallenging to teach reading. Good teaching has to apply a goodstrategy to encourage the students to be involved in the classactivities. One of the strategies is using semantic mapping. Accordingto Thomas, H. Estes (1999) Semantic Mapping is a strategy thatallows the students to organize their prior knowledge in these formalrelations, and thus provide themselves a basis for understanding whatthey are about to read and study. Semantic mapping provides agraphic structure of the knowledge that can be used to organize newideas as they are understood.